Election cycles in European public procurement - Annika Havlik; Friedrich Heinemann; Justus Nover (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
This paper studies the existence of election cycles in public procurement in the European Union for the national level. We analyze different steps along the procurement process, namely the publication of the contract notice, the awarding of the contract, and the project completion. We point out how these steps should differ in their potential to address specific types of voters. We argue that the award provides politicians with a particularly appealing opportunity. It allows them to please the award-winning firms' stakeholders and the spending decision becomes binding and credible also from the perspective of forward-looking voters. We find robust evidence for electioneering in contract notices and awards prior to national parliamentary elections. The effect in contract awards is particularly strong for certain sub-categories like education and is more pronounced for visible projects.
Keywords: D72; D73; H57; 330; Forward-looking voters; political budget cycles; retrospective voting; Tenders Electronic Daily (TED)